Analisis Framing Pemberitaan Online Amsakar Achmad sebagai Calon Walikota Batam Potensial pada Media Online Batampos.co.id dan Batamnews.co.id - Riswandi; Sholihul Abidin; Lingga Angling Wulung; Anisa Rifqi Aulia; Encah Herlina (PT. PENERBIT TIGA MUTIARA, 2024)
This study aims to identify and analyze the framing used by BatamPos.co.id and BatamNews.co.id in their coverage of Amsakar Achmad as a candidate for Mayor of Batam, compare the framing employed by these two media outlets, and assess the impact of such framing on public perception. This qualitative research utilizes framing analysis based on framing theory. Primary data consists of news articles from BatamPos.co.id and BatamNews.co.id published during the period of May-June 2024. Secondary data is derived from literature related to framing theory and previous studies. Data collection was conducted through purposive sampling, and analysis was performed by identifying main themes, categorizing the news coverage, and evaluating the impact of framing on public perception. The analysis reveals that the framing of news about Amsakar Achmad on BatamPos.co.id tends to emphasize strong political support, popularity, and Amsakar’s concrete visions and programs. In contrast, BatamNews.co.id focuses more on Amsakar’s direct interactions with the public, local community support, and political communication. Both media construct a positive image of Amsakar, albeit with different approaches. BatamPos.co.id creates the perception that Amsakar is a strong candidate with solid political backing and a clear plan for Batam’s progress, while BatamNews.co.id portrays Amsakar as a leader who is close to the people, adaptive, and collaborative. This research provides insights into how media framing can influence public perception of political candidates.